2019
DOI: 10.1186/s40360-019-0309-7
|View full text |Cite
|
Sign up to set email alerts
|

Epinecidin-1, a highly potent marine antimicrobial peptide with anticancer and immunomodulatory activities

Abstract: Background Antibiotic-resistant pathogens are an emerging threat in this century. Epinecidin-1 is a multi-functional Antimicrobial Peptide (AMP) produced by Orange-spotted grouper ( Epinephelus coioides ) has been shown to have extensive potentials as an alternative for current antibiotics. Due to the huge costs for the study and the production of a new drug, if an antimicrobial peptide has other beneficial functions in addition to antimicrobial activities, it would be p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(18 citation statements)
references
References 62 publications
0
18
0
Order By: Relevance
“…Fish immunity consists of two components, innate and adaptive immune system [ 97 ]. Recent studies revealed that cytokines play appreciable innate immune factors in fish which displayed as antibacterial, antifungal, antiviral and antiprotozoal agents [ 98 ]. The gut-associated lymphoid tissues (GALT) contain a variety of immune cells and play a critical role in maintaining the balance between pathogenic and commensal microbiota [ 99 ].…”
Section: Discussionmentioning
confidence: 99%
“…Fish immunity consists of two components, innate and adaptive immune system [ 97 ]. Recent studies revealed that cytokines play appreciable innate immune factors in fish which displayed as antibacterial, antifungal, antiviral and antiprotozoal agents [ 98 ]. The gut-associated lymphoid tissues (GALT) contain a variety of immune cells and play a critical role in maintaining the balance between pathogenic and commensal microbiota [ 99 ].…”
Section: Discussionmentioning
confidence: 99%
“…Antiparasitic peptides show their killing effect on parasites which cause diseases such as malaria and leishmaniasis (Mangoni et al, 2005;Rhaiem and Houimel, 2016) and AMPs like cathelicidin, temporins-SHd show high inhibition activity against parasites (Abbassi et al, 2013). In recent research, Epi-1, a marine synthetic AMP, can remarkably inhibit Trichomonas vaginalis by destroying its membrane (Neshani et al, 2019). The peptide Jellein derived from bee royal jelly which has introduced above and 4-amino acid AMP KDEL (lysine, aspartic acid, glutamic acid, and leucine) has shown a significant effect on the Leishmania parasite (Cao et al, 2019;Zahedifard et al, 2020).…”
Section: Antiparasitic Peptidesmentioning
confidence: 99%
“…Increasing antibiotic-resistant microorganisms is one of the most serious problems in health care systems. [13][14][15][16][17][18] One of the most common antibiotic-resistant bacteria is MRSA. Identification of MRSA contaminated staff in hospital wards can prevent the spread of this type of resistance.…”
Section: Discussionmentioning
confidence: 99%